Recent Advances in Strain-Release Functionalization of [1.1.1]Propellanes Using Organometallic Reagents - Dhayalan, Vasudevan (Synlett, 2025)
The highly strained bicyclic hydrocarbon bicyclo[1.1.1]propellane has emerged as a versatile scaffold in synthetic organic and medicinal chemistry due to the remarkable structural reactivity of its central bond between the two bridgehead carbons. Over the past decade, many research groups have harnessed this strain-release reactivity to advance an efficient synthetic approach for constructing bicyclo[1.1.1]pentane (BCP) scaffolds. This review presents a comprehensive overview of the most recent advancements in the functionalization of bicyclo[1.1.1]propellane using commercially accessible organometallic reagents (RMX). Organo-lithium, magnesium, zinc, and boron reagents have demonstrated excellent ring-opening reactivity under mild and sustainable conditions, furnishing highly functionalized 1,3-disubstituted BCP derivatives and related amine scaffolds in excellent yields, acting as broad functional group tolerant, eco-friendly, and low-toxicity reagents. These organometallic reagent–mediated strain-release functionalization methods are expected to have noteworthy synthetic utility, mostly in medicinal and pharmaceutical chemistry.
Keywords: Bicyclo[1.1.1]pentane; Bicyclo[1.1.1]propellane; Catalysis; Organometallic reagents; Cross-coupling